Mentoring Children with Learning Difficulties in Inclusive Primary Schools - nursaptini, nursaptini; nzobonimpa, claver; sobri, muhammad; novitasari, setiani; Indraswati, dyah; sutisna, deni (Jurusan Pendidikan Luar Biasa, 2020)
This study aims to determine the learning process for children learning difficulties in inclusive schools in elementary schools. This research is qualitative research with a case-study approach. The study was conducted at SDN 1 Sangkawana Batukliang District, Central Lombok Regency. Subjects in this study were the Principal, Low - grade teacher Data collection through non-participant observation, semi-structured interviews and documentation. Data analysis was performed using the Spiral Analysis model developed by Creswell. Research Findings that teacher competencies in the service of children with learning difficulties need to be possessed. The teacher is a determinant of the success of the learning process especially for children with learning difficulties who need more guidance in learning. In general, the learning process for children with learning difficulties in inclusive schools is the same as regular schools. The difference is in the provision of learning activities and services that are more remedial. This is done starting from the teacher doing adaptation in designing the Learning Implementation lesson plan by the circumstances of the students